Does TQM impact on role stressors? A conceptual model - Teh, Pei-Lee; Ooi, Keng-Boon; Yong, Chen-Chen (EMERALD GROUP PUBLISHING LIMITED, 2008)
Purpose - The purpose of this paper is to develop a conceptual model to examine the multidimensionality of total quality management (TQM) practices and its impact on role stressors.